Bacterial Meningitis as a complication of Urosepsis: A case report - Nagpal, Chand; Maharani, Kartika; Estiasari, Riwanti; Imran, Darma (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2025)
Bacterial meningitis is a severe bacterial infection that infiltrates the meninges and is characterized by headache, fever and neck stiffness. We present a case of a 60-year-old female with urosepsis consulted to the neurology department with loss of consciousness. Her clinical symptoms progressed over 7 days, with loss of consciousness, fever, meningeal signs and right-sided hemiparesis, suggestive of acute meningitis. Lumbar puncture was performed and CSF analysis suggested partially treated meningitis. Blood culture revealed growth of Enterococcus faecalis. Intravenous dexamethasone and meropenem were given and oral antibiotics were continued until the patient regained consciousness completely. Bacterial meningitis should be suspected in any severe systemic infection with clinical symptoms such as loss of consciousness. Establishing a diagnosis with the help of CSF analysis, culture, and appropriate treatment with antibiotic selection and dosage is imperative to ensure adequate penetrance to the central nervous system. Physician’s clinical judgement to establish an early diagnosis and initiate treatment is crucial and determines patient outcome. Initial phase of BM can be clinically severe, and often requires treatment in the ICU initially.